296. SARS-CoV-2 Illness Severity and Early Hospitalization Outcomes in a Multicenter Prospective Cohort Study Among Veterans. (15th December 2022) - Ross, Jennifer M; Sugimoto, Jonathan D; Timmons, Andrew; Moore, Kathryn; Adams, Jonathan; Wilson, Deanna; Liu, Cindy H; Deardoff, Katrina V; Korpak, Anna; Chang, Kyong-Mi; Cho, Kelly; Crothers, Kristina; et al.
Abstract: Background: Over 600, 000 SARS-CoV-2 infections and 20, 000 deaths have occurred among users of the Veterans Health Administration, the US's largest integrated health care system. We explored early outcomes of SARS-COV-2 infection in Veterans. Methods: An ongoing, prospective longitudinal cohort study of Veterans ages ≥ 18 enrolled 1, 826 participants (29.0% inpatient; 49.1% vaccinated; 68.3% SARS-CoV-2-positive; 85.0% male, mean age = 57.1 years) seeking inpatient or outpatient care after SARS-CoV-2 testing at 15 Department of Veterans Affairs medical centers in July 2020 to February 13, 2022. Using multivariable regression, we estimated relationships of baseline demographic characteristics, COVID-19 vaccination, and clinical history to illness severity and cumulative length of hospital stay within 60 days of study entry. Illness severity was defined by a Veterans Affairs adaptation of the WHO COVID-19 severity scale and included 4 levels (mild, moderate, severe, or death). We derived the Charlson co-morbidity index (CCI) and other baseline characteristics from electronic health data and study questionnaires, and reported qualitative SARS-CoV-2 IgG responses using inpatients' study-collected blood specimens. Results: High CCI scores (≥ 5) occurred in 47 (42.7%) vaccinated SARS-CoV-2-positive inpatients and 47 (21.2%) unvaccinated. Severe illness occurred in 17 (15.5%) vaccinated inpatients, 37 (16.7%) unvaccinated inpatients, 4 (0.9%) vaccinated outpatients, and 3 (0.7%) unvaccinated outpatients. Eleven (10%) of 110 vaccinated SARS-CoV-2-positive inpatients died, as did 15 (6.8%) of the 222 unvaccinated. In SARS-CoV-2-positive inpatients, a one-step higher CCI was associated with more severe illness (aOR 1.10, 95% CI 1.01-1.20) and more hospitalization days (aIRR 1.06, 95% CI 1.03-1.10), adjusting for vaccination status. Respectively, 93% of vaccinated and 63% of unvaccinated SARS-CoV-2 positive inpatients with baseline antibody results had an anti-spike IgG response. Conclusion: In an ongoing longitudinal cohort study of COVID-19 in US Veterans, comorbidity burden was higher among vaccinated than unvaccinated inpatients and was associated with more severe illness and hospitalization days, independent of vaccination status. Disclosures: Christine M. Hunt, MD, MPH, Adaptive Phage Therapeutics: Advisor/Consultant|Akebia: Advisor/Consultant|Galmed: Advisor/Consultant|Otsuka: Advisor/Consultant|Palladio: Advisor/Consultant.